Plateforme de Mesures Aéroportées - Coutris, Pierre; Schwarzenboeck, Alfons (OPGC, LaMP, 2023)
The Airborne Measurement Platform (PMA) is a set of scientific instruments used to characterize the microphysical and optical properties of cloud particles in situ. It is carried on research aircraft, such as the French SAFIRE fleet for example, during airborne measurement campaigns. The PMA has been labeled "National Instrument" by INSU since 2008. As such, it is made available to the entire national scientific community. The data collected during the campaigns is also made available to the community, depending on the projects and the applicable internal data management policy.